Unveiling Science Edupreneurship: Perspective Analysis on Trends and Impact on SDGs - Sunarti, Titin; Hariyono, Eko; Isnawati, I; Sunni, Fajriatul Mufarriha; Dawana, Irgy Redityo; Wardi, Ladika Zuhrotul; Arivi, Maharani Agustina (Studies in Learning and Teaching, 2025)
In this dynamic era, introducing entrepreneurship into science education can produce entrepreneurial-minded graduates capable of creating independent businesses. This concept is essential in basic science, enabling the use of scientific concepts to develop innovative solutions. This research aims to explore the trends in science edupreneurship and its impact on SDGs through bibliometric analysis. The literature review and Meta-Analyses (PRISMA) method were used in this study, combined with bibliometric analysis using the Scopus database. The findings show that research on science edupreneurship has increased significantly over the last 10 years. The most common document type is articles, with the majority of sources coming from journals, and the most publications contributed by the United States of America. The results of this study provide a broad overview of the importance of integrating science edupreneurship and its impact on SDGs. The mapping results also offer several strategic recommendations, including the need to further develop interdisciplinary approaches to meet the challenges of education and innovation. Additionally, the use of educational technology and innovative teaching methods should be considered to enhance learning effectiveness. International collaboration among researchers and institutions is also necessary to share knowledge and develop effective strategies. Education tailored to the individual needs of students is recommended to ensure effective learning. Integration with local communities and industries can increase the relevance of education to the relevance of industries’ needs.